Strategies for Strengthening Critical Thinking Through Active Learning Aqidah Akhlak in State MTs in Kediri City - Mustamir, Ahmad Khoirul (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The issue of critical thinking skills in the face of the challenges of the Industrial Revolution 4.0 era is a significant one. The prevalence of information and rapid knowledge services through technology can potentially lead students to neglect their critical thinking skills. This is particularly true in doctrinal subjects such as Aqidah Akhlak. The impact of this trend is evident in the learning process of Akidah Akhlak subjects at MTsN in Kediri City. The research focuses on the role of Active Learning strategies in supporting students to develop critical thinking skills through participatory learning. The qualitative research method was implemented through non-participant observation, interview, and document analysis approaches. The researcher explored the interaction between teachers and students in the implementation of Active Learning strategies, as well as assessing students’ responses to the learning process centered on active participation and critical reflection. The results showed that the construction of Active Learning strategies in State MTs in Kediri City was built in response to the demands of the times. In practice, the construction of this strategy is supported by government regulations, internal madrasah policies, educational theories, teacher readiness, and the availability of facilities and infrastructure. Active Learning strategies are implemented through systematic planning, implementation, and evaluation stages. The Active Learning strategy has been proven highly effective in strengthening students’ critical thinking skills, providing reassurance about the positive impact of these strategies. With continuous support, this strategy has the potential to become a relevant and transformative learning model in forming an adaptive and solution-oriented Islamic generation.